Vetra. Artefacto para la disminución de dolor físico en las actividades diarias de pacientes con cáncer de cuello uterino (2021)
Patients with cervical cancer in Latin America must suffer a series of daily bodily difficulties due to the pain caused by the side effects of the treatments for the disease. These women have been forced to stop their daily activities due to a series of physical symptoms that affect them emotionally. In order to respond to this need, a methodological construction is made from fragments of different authors that allows to obtain a personalized methodology for the project. Additionally, in order to understand more closely these ailments and needs of patients, interviews and surveys were conducted to understand their corporeality. As a result, Vetra is a device of physical assistance that thanks to its functions manages to reduce cancer pain and thus facilitate daily tasks, in addition to contributing to the improvement of the personal perception of each woman.